Association of apolipoprotein E ε4 allele and amyotrophic lateral sclerosis in Chinese population. Issue 5 (3rd July 2022) - He, Di; Shang, Liang; Liu, Qing; Shen, Dongchao; Sun, Xiaohan; Cai, Zhengyi; Zhao, Ximeng; Liu, Liyang; Yang, Xunzhe; Liu, Mingsheng; Zhang, Xue; Cui, Liying
Abstract: Background : Amyotrophic lateral sclerosis (ALS) has a complex genetic origin, and how immune dysregulation may contribute to ALS etiology remain unclear. Given the roles played by apolipoprotein E (APOE) signaling in neuroinflammation and neurodegeneration, an improved knowledge of the association between APOE genotypes and ALS risk in Chinese population may help to understand the underlying etiology of the disease. Methods: A retrospective case-control study with participants of Chinese ancestry was conducted, with a total of 683 ALS patients and 369 healthy controls analyzed for APOE genotypes using Sanger sequencing. In addition, 282 of these patients were further analyzed for known ALS risk variants and rare deleterious variants related to immune disorders via whole exome sequencing. Results: Among the 683 ALS patients analyzed (346 males, 337 females; mean age at onset [SD]: 51.9 [10.9]), 145 patients (21.1%) carried ε4, the proportion of which was significantly higher than 16.0% in controls (59/369; OR, 1.42; 95%CI, 1.02–1.98; p  = 0.02). There is no evidence supporting the association between APOE genotypes and disease phenotypes. We also didn't find any enrichment of currently known ALS risk variants or variants in genes related to immune abnormality in specific APOE genotypes. Conclusion: Our study highlighted the importance of trans-ethnic studies in identifying genetic risk factors, and the relevance of APOE in ALS etiopathogenesis in Chinese population.